Asymmetric synthesis of p-stereogenic homo- and hetero-bimetallic complexes via monoinsertion of di(phenylethynyl)phenylphosphine into the Pd-C bond of orthopalladated naphthylamine promoted by cyclometallated template. - Quek, Sharon Su Ping. (2010)
Both napthylamine and benzylamine chiral cyclopalladated and cycloplatinated template have been used for monoinsertion of di(phenylethynyl)phenylphosphine ligand into the Pd-C bond of orthopalladated naphthylamine. These insertions proved to be possible under mild reaction conditions and resulted in a series of regioselective complex: including homo- or heterodimetallic compound incorporating the new generated P-chiral center. Among which, the major product produced adopted the R configuration. However, there is an exception to the experiment whereby the expected configuration was not obtained. The coordination chemistry and the stereochemistry of the insertion products and transformation products were deduced by X-Ray crystallography. And the effectiveness of the metal template was discussed.